Delphi consensus recommendations on how to provide cardiovascular rehabilitation in the COVID-19 era. (7th November 2020) - Ambrosetti, Marco; Abreu, Ana; Cornelissen, Veronique; Hansen, Dominique; Iliou, Marie Christine; Kemps, Hareld; Pedretti, Roberto Franco Enrico; Voller, Heinz; Wilhelm, Mathias; Piepoli, Massimo Francesco; Beccaluva, Chiara Giuseppina; Beckers, Paul; et al.
Abstract: This Delphi consensus by 28 experts from the European Association of Preventive Cardiology (EAPC) provides initial recommendations on how cardiovascular rehabilitation (CR) facilities should modulate their activities in view of the ongoing coronavirus disease 2019 (COVID-19) pandemic. A total number of 150 statements were selected and graded by Likert scale [from −5 (strongly disagree) to +5 (strongly agree)], starting from six open-ended questions on (i) referral criteria, (ii) optimal timing and setting, (iii) core components, (iv) structure-based metrics, (v) process-based metrics, and (vi) quality indicators. Consensus was reached on 58 (39%) statements, 48 'for' and 10 'against' respectively, mainly in the field of referral, core components, and structure of CR activities, in a comprehensive way suitable for managing cardiac COVID-19 patients. Panelists oriented consensus towards maintaining usual activities on traditional patient groups referred to CR, without significant downgrading of intervention in case of COVID-19 as a comorbidity. Moreover, it has been suggested to consider COVID-19 patients as a referral group to CR per se when the viral disease is complicated by acute cardiovascular (CV) events; in these patients, the potential development of COVID-related CV sequelae, as well as of pulmonary arterial hypertension, needs to be focused. This framework might be used to orient organization and operational of CR programmes during the COVID-19 crisis.